Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Pelanggan Pada TIKI Cabang Utama Samarinda - Dahlia, Dorce Dahlia (EKONOMIA, 2019)
Dorce Dahlia Â : The Influence of Service Quality and Trust on Satisfaction At TIKI Main Branch of Samarinda. This study aims to determine the effect: 1) tangible to customer satisfaction At TIKI Main Branch Samarinda; 2) empathy towards customer satisfaction At TIKI Main Branch of Samarinda; 3) reliability of customer satisfaction At TIKI Main Branch of Samarinda; 4) responsiveness to customer satisfaction At TIKI Main Branch of Samarinda; 5) confidence in customer satisfaction At TIKI Main Branch of Samarinda; 6) trust in customer satisfaction At TIKI Main Branch Samarinda and 7) tangible, empathy, reliability, responsiveness, belief and trust simultaneously to customer satisfaction At TIKI Main Branch Samarinda.The research population used by the researcher is all students of the University of 17 August 1945 Samarinda in the period of 2013/14 - 2016/17 which amounted to 6,172 students. The sample was 98 students with slovin formula and sample selection using proportionate stratified random sampling technique. Data analysis technique used multiple linear regression analysis with classical assumption test and hypothesis test. The findings of this study are tangible variables have a positive and significant impact on customer satisfaction in TIKI Main Branch Samarinda, empathy variable does not have a negative and insignificant effect on customer satisfaction in TIKI Main Branch Samarinda, reliability variables have a positive and significant impact on customer satisfaction on TIKI Main Branch Samarinda , the variable of responsiveness does not have a positive and insignificant effect on customer satisfaction in TIKI Main Branch of Samarinda, confidence variable has no positive and insignificant effect to customer satisfaction at TIKI Main Branch of Samarinda, trust variable has no positive and insignificant effect to customer satisfaction at TIKI Branch Main Samarinda, intangible variables, empathy, reliability, responsiveness, belief and trust simultaneously have a positive and significant impact on customer satisfaction at TIKI Main Branch of Samarinda